Traditional Indonesian Medication Combats COVID-19 - Yanuar, Arry; Hasanah, Nur; Chany Saputri, Fadlina; Bustamam, Alhadi (KnE Social Sciences, 2023)
In Indonesia, the number of cases infected with Covid-19 peaked between mid-June and August 2021, resulting in the denial of hospital treatment to some people due to insufficient capacity. Therefore, people treat themselves by using natural ingredients. This study aims to identify plants that can treat Covid-19 with self-medication. This study took a description approach to investigate people using traditional herbs in self-medication for COVID-19 recovery. Snowball sampling is the approach used. Interviews and an online system (gform) were used to collect data. The number of samples collected allows for a more thorough analysis of the 104 respondents. The results showed that women (51.0%), people aged between 56 and 65 (52.9%), Banten residents (32.7%), secondary education (57. 7%), and people with comorbidities (86.5). %) were all interested in using traditional herbal medicine. Reduction of symptoms and results of laboratory tests were used to measure recovery. The most common comorbidities were hypertension (7-14 days to recovery), diabetes mellitus (15-21 days to recovery), and cardiovascular disease (7-14 days and 15-21 days to recovery). The Zingiberaceae family dominates traditional herbs. The most widely used traditional ingredients are Empon-Empon, which consists of red ginger, turmeric, nutmeg, aromatic ginger, bay leaves, lemongrass, galangal, cinnamon, and cloves. The average healing time is 7-14 days (32.7%). In conclusion people who utilized herbal medicines reported a speedy recovery and reduction in the severity of their symptoms. Keywords: Covid-19, Empon-Empon, herbal medicine, self-medication, traditional ingredients